Microscopic Structural and Dynamic Features in Triphilic Room Temperature Ionic Liquids - Lo Celso, Fabrizio; Appetecchi, Giovanni B.; Simonetti, Elisabetta; Zhao, Man; Castner, Edward W.; Keiderling, Uwe; Gontrani, Lorenzo; Triolo, Alessandro; Russina, Olga (Frontiers in Chemistry, 2019)
Here we report a thorough investigation of the microscopic and mesoscopic structural organization in a series of triphilic fluorinated room temperature ionic liquids, namely [1-alkyl,3-methylimidazolium][(trifluoromethanesulfonyl)(nonafluorobutylsulfonyl)imide], with alkyl=ethyl, butyl, octyl ([Cnmim][IM14], n=2, 4, 8), based on the synergic exploitation of X-ray and Neutron Scattering and Molecular Dynamics simulations. This study reveals the strong complementarity between X-ray/neutron scattering in detecting the complex segregated morphology in these systems at mesoscopic spatial scales. Use of MD simulations delivering very good agreement with experimental data allows gaining a robust understanding of the segregated morphology. The structural scenario is completed with determination of dynamic properties accessing the diffusive behaviour and a relaxation map is provided for [C2mim][IM14] and [C8mim][IM14], highlighting their natures as fragile glass formers.